2005
DOI: 10.1111/j.1600-0404.2005.00300.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxcarbazepine monotherapy in postherpetic neuralgia unresponsive to carbamazepine and gabapentin

Abstract: Oxcarbazepine appears to be a promising alternative monotherapeutic approach for patients affected by PHN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…However, rapid onset of action was noticed with fixed dose pregabalin which may reflect the higher dose during the first week of treatment with this regime (103). Recent studies have evaluated the effectiveness and safety of oxcarbazepine and divalproex sodium (valproic acid and sodium valproate) for the treatment of postherpetic neuralgia (104,105). In an open-label trial, oxcarbazepine monotherapy administered for 8 weeks resulted in a statistically significant effect on pain reduction, allodynia and improvement in quality of life among patients with post-herpetic neuralgia (104).…”
Section: Anticonvulsantsmentioning
confidence: 99%
“…However, rapid onset of action was noticed with fixed dose pregabalin which may reflect the higher dose during the first week of treatment with this regime (103). Recent studies have evaluated the effectiveness and safety of oxcarbazepine and divalproex sodium (valproic acid and sodium valproate) for the treatment of postherpetic neuralgia (104,105). In an open-label trial, oxcarbazepine monotherapy administered for 8 weeks resulted in a statistically significant effect on pain reduction, allodynia and improvement in quality of life among patients with post-herpetic neuralgia (104).…”
Section: Anticonvulsantsmentioning
confidence: 99%
“…The optimal dose to be administered has not yet been thoroughly assessed. Other recently studied antiepileptic drugs are sodium divalproate and oxcarbazepine, which demonstrated a significant efficacy in reducing pain and improving patient quality of life 96,97…”
Section: Resultsmentioning
confidence: 99%
“…Capsaicin formulations are promising (level A), but the long-term effects of repeated applications are not well described, particularly on sensation 68,102. Other antiepileptic drugs (valproate) may be associated in patients with inadequate pain relief or intolerance to previously indicated medications 96,97…”
Section: Discussionmentioning
confidence: 99%
“…A small open-label trial suggested it was effective for postherpetic neuralgia in patients who got no relief from carbamazepine and gabapentin. 52 In a larger placebo-controlled trial, 53 patients with painful diabetic neuropathy for at least 6 months had significantly better pain scores than at baseline after treatment with oxcarbazepine, suggesting it has a role as monotherapy in chronic painful diabetic neuropathy.…”
Section: Lidocaine Patches Should Be Worn For 12 Hours On 12 Hours Offmentioning
confidence: 99%